Do they have designs on us or for us? (or Beware of Greeks bearing gifts) - Jarman, Dik (2015)
In this paper I am proposing that for a regional project designed by foreign entities to be truly successful the understanding of the culture of the key stakeholders needs to be two way. Not only does the designer need to learn and understand the relevant regional aspects for which they are designing but the client and relevant stakeholders of that project need to understand the culture of those proposing the design for the necessary trust and understanding to facilitate an excellent outcome. This two-way understanding is key in maximising the International Transferability of Urban Design Skills.